2012
DOI: 10.4103/0970-4388.95581
|View full text |Cite
|
Sign up to set email alerts
|

Nature of feeding practices among children with cleft lip and palate

Abstract: Spoon feeding was found as the most common feeding method practiced by the parents of children with cleft lip and palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 0 publications
1
27
0
6
Order By: Relevance
“…Another study conducted to identify the feeding practices among children with cleft lip and palate in different age ranges concluded that spoon feeding was the most common feeding method (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted to identify the feeding practices among children with cleft lip and palate in different age ranges concluded that spoon feeding was the most common feeding method (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, the glass and spoon are viable alternatives due to their low cost, easy handling and hygiene. A study (3) compared the food acceptance of children in the immediate postoperative period after palatoplasty using glass and spoon, and evidenced that children fed with the spoon accepted greater volume in shorter time, with fewer cases of cough and choking and less food loss through the lip commissure.Another study conducted to identify the feeding practices among children with cleft lip and palate in different age ranges concluded that spoon feeding was the most common feeding method (13) .Other utensils are described in the literature as alternatives for child feeding after cheiloplasty and palatoplasty, including syringes, tubes and droppers. However, these are not often used anymore, and their utilization is associated with lack of information.…”
mentioning
confidence: 99%
“…Some of the authors have advocated the use of obturators during the feeding of affected infants. 6,7 The concept of naso-alveolar molding combines the obturator with the active components for molding the growth of intraoral cleft segments along with feeding. However, with the obturator and the naso-alveolar molding techniques, the focus is not on definitive and exclusive breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 compares the Z score (weight) at each visit between the three groups. WHO classifies the weight based on SD from the median as normal, mild to moderate and severe malnutrition [8].…”
Section: Resultsmentioning
confidence: 99%